Distribution of wetlands in Argentina estimated from soil charts - DOI: 10.4025/actascibiolsci.v30i4.5870 - Patricia Kandus; Priscila Minotti; Ana Inés Malvárez (Acta Scientiarum. Biological Sciences, 2008)
We generated a map of wetlands in Argentina from the digital edition of the National Soil Inventory made by the National Institute of Agricultural Technology (Instituto Nacional de Tecnología Agropecuaria, INTA). Potential wetland areas were extracted from the map after an exhaustive analysis of the database and reassignment of the soil classes, by taking into account 1) soil taxonomic classes; 2) constraining factors (waterlogging, flooding, drainage impairment); and 3) cartographic categories, including lakes, lagoons, marshes and salt lakes. Estimated wetland area is about 600,000 km2, representing 21.5% of the national territory; it increases to 23% when considering salt lakes and deepwater bodies, but their surface is underestimated in the INTA database. Finally, we analyzed the distribution and abundance of wetland areas from different eco-regions of Argentina, and compared our results with current global wetland databases.